(untitled) (Journal of Environmental Science and Natural Resources, 2015)
Experiments were conducted in the laboratory of the Division of Entomology, Bangladesh Institute of Nuclear Agriculture (BINA), Mymensingh to evaluate the efficacy of four indigenous plants parts such as leaves of raintree (Albizia saman), riot lata (Mikania micrantha), pithraj (Aphanamixis polystachya) and seeds of mahogani (Swietenia macrophylla) with methanol extracts at the rates of 10.0, 7.5, 5.0 and 2.5% for their direct toxicity against the pulse beetle, Callosobruchus chinensis (L.). The experiments were set up following Completely Randomized Design (CRD). The results showed that extracts of all the plant parts had very close efficacy in relation to direct toxicity effect and grain protection values. Pithraj leaf extract showed the highest mortality (96.66%) action and raintree leaf extract showed the lowest (80.33%) with 10% extract at 5 DAT. The effectiveness of all the plant extracts were found to increase with the increase of doses and decreased proportionatelly with the increase of time DOI: http://dx.doi.org/10.3329/jesnr.v7i2.22206 J. Environ. Sci. & Natural Resources, 7(2): 65-67 2014